High‐Performance Organic Electrochemical Transistors and Neuromorphic Devices Comprising Naphthalenediimide‐Dialkoxybithiazole Copolymers Bearing Glycol Ether Pendant Groups. (8th April 2022) - Zhang, Yanxi; Ye, Gang; van der Pol, Tom P. A.; Dong, Jingjin; van Doremaele, Eveline R. W.; Krauhausen, Imke; Liu, Yuru; Gkoupidenis, Paschalis; Portale, Giuseppe; Song, Jun; Chiechi, Ryan C.; van de Burgt, Yoeri
Abstract: Organic electrochemical transistors (OECTs) have emerged as building blocks for low power circuits, biosensors, and neuromorphic computing. While p‐type polymer materials for OECTs are well developed, the choice of high‐performance n‐type polymers is limited, despite being essential for cation and metabolite biosensors, and crucial for constructing complementary circuits. N‐type conjugated polymers that have efficient ion‐to‐electron transduction are highly desired for electrochemical applications. In this contribution, three non‐fused, planar naphthalenediimide (NDI)‐dialkoxybithiazole (2Tz) copolymers, which systematically increase the amount of polar tri(ethylene glycol) (TEG) side chains: PNDI2OD‐2Tz (0 TEG), PNDIODTEG‐2Tz (1 TEG), PNDI2TEG‐2Tz (2 TEG), are reported. It is demonstrated that the OECT performance increases with the number of TEG side chains resulting from the progressively higher hydrophilicity and larger electron affinities. Benefiting from the high electron mobility, excellent ion conduction capability, efficient ion‐to‐electron transduction, and low‐lying lowest unoccupied molecular orbital energy level, the 2 TEG polymer achieves close to 10 5 on‐off ratio, fast switching, 1000 stable operation cycles in aqueous electrolyte, and has a long shelf life. Moreover, the higher number TEG chain substituted polymer exhibits good conductance state retention over two orders of magnitudes in electrochemical resistive random‐access memory devices, highlighting its potential for neuromorphic computing. Abstract : Non‐fused, planar naphthalenediimide‐dialkoxybithiazole conjugated polymers bearing polar tri(ethylene glycol) (TEG) are designed for electrochemical applications, such as organic electrochemical transistors (OECTs) and electrochemical resistive random‐access memory devices (EC‐RAMs). The higher TEG chain substituted polymer exhibits outstanding performance for OECTs and excellent conductance state retention for EC‐RAMs.